Unfit for Subjection: Mental Illness, Mental Health, and the University Undercommons - Hankins, Sarah (Current Musicology, 2021)
This colloquy, by graduate-student-led collective Project Spectrum, attempts to map out existing discussions around inclusion and equity in music academia, with a specific focus on identifying and analyzing the structures in academia that work against minoritized and historically excluded scholars. Sarah Hankins shares thoughts on mental illness, arguing that it is a gap in our discourse. Hankins asks us to bear witness to experiences of those who boldly declare that they are “unfit” for the pipeline—“unfit” to survive the pipeline, to have access to the pipeline, and for the so-called promises at the end of the pipeline. Following the work of Black studies, queer of color critique, Black radicalism, Afropessimism, and especially the writings of Stefano Harney and Fred Moten, Hankins’s intervention in this colloquy demands pause in academia’s system of perpetual motion.